Dampak Alih Fungsi Lahan terhadap Eksistensi Subak Kedungu, di Desa Pererenan, Kecamatan Mengwi, Kabupaten Badung - LESMANA, I KADEK ADI YOGA; SUAMBA, I KETUT; ASTITI, NI WAYAN SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.2, Desember 2022, 2022)
The Impact of Land Functions on the Existence of Subak Kedungu, Pererenan Village, Mengwi District, Badung Regency Subak is very thick in community life in Bali. Subak is closely related to Tri Hita Karana, which is a guideline for the community in religious social activities carried out by the indigenous community in Bali.The purpose of this study is to determine the impact of land use change and the causes of land use change on the existence of Subak Kedungu in terms of social, economic and technical aspects.The location of this research was conducted in Subak Kedungu, Pererenan Village, Mengwi District, Badung Regency from November 2020 to January 2021.The selection of the research location was carried out by using the perposive method using key informants.The determination of informants in this study involved all elements related to the Kedungu Subak, such as members of the subak, subak landowners, subak members who sold land, tenants, tenants, subak institutions, and village institutions.The results showed the causes of land conversion that occurred in Subak Kedungu, among others, an increase in the number of family members, an increase in community needs, and a decrease in the interest of young people in Pererenan Village to replace their parents as farmers.Meanwhile, the impact of land conversion that occurs is that the social aspects do not have an impact on the community, the economic aspect of income from farming does not experience a reduction, and the technical aspects are not too affected because basically the members of Subak Kedungu only plant rice.